2009
DOI: 10.1055/s-0029-1224096
|View full text |Cite
|
Sign up to set email alerts
|

Acute Subdural Hematoma in the Elderly; Clinical and CT Factors Influencing the Surgical Treatment Decision

Abstract: Patients with a GCS of 13-15 can be observed clinically (the expected outcome is very good). Comatose patients (GCS 3-8) with bilateral dilatation of the pupils should not be operated (very high mortality rate). If the GCS score is <13 and both pupils or only one are reactive to light and the midline shift<10 mm, surgery is indicated. If the midline shift is >10 mm and aSDH thickness>midline shift, surgery is also indicated. If in the same patient group midline shift>SDH thickness and ICP>40 mmHg, surgery is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 14 publications
4
59
1
Order By: Relevance
“…Kilaru et al (20) have also pointed out that TBI patients more than 65 years of age with GCS below 8 points demonstrated vegetative state, or dependent living in a facility and all patients with GCS score of 3 points died. Thus, low GCS has been found to be the strongest unfavorable predictive factor for elderly patients who suffered from ASDH (33,38). Surgical management in this study, however, was associated with better outcome and lower mortality for elderly patients who suffered from ASDH and had GCS scores of 6 or above (Tables 4 and 7).…”
Section: Discussionmentioning
confidence: 53%
“…Kilaru et al (20) have also pointed out that TBI patients more than 65 years of age with GCS below 8 points demonstrated vegetative state, or dependent living in a facility and all patients with GCS score of 3 points died. Thus, low GCS has been found to be the strongest unfavorable predictive factor for elderly patients who suffered from ASDH (33,38). Surgical management in this study, however, was associated with better outcome and lower mortality for elderly patients who suffered from ASDH and had GCS scores of 6 or above (Tables 4 and 7).…”
Section: Discussionmentioning
confidence: 53%
“…The association between severity of disease and poor outcome has been described in numerous other studies on SDH. 10,19,24,34,35 Similarly, comorbidities such as cardiac and renal disease and coagulopathy have been associated with worse outcomes as well. 8,20 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…1 Also, a cohort study done by Baechli et al 5 showed that of 354 patients, those older than 65 years of age had rates of mortality similar to those of younger patients after undergoing neurosurgical interventions for subdural hematoma. Age may not be an adequate indicator for likelihood of postsurgical recovery; rather a clinical metric of frailty 32 and other preoperative parameters 22 have been shown to be effective in predicting survival rates postoperatively. Also, regarding the value of neurosurgical treatment among the elderly, a recent study showed that patients 70 years and older with subarachnoid hemorrhages had favorable clinical outcomes, and concluded that age should not preclude treatment.…”
Section: Discussionmentioning
confidence: 99%